Comparative analysis of the key factors influencing healthcare systems of oecd countries - Katarzyna M. Miszczyńska (e-Finanse: Financial Internet Quarterly, 2018)
The Health sector, as a part of the national economy, is extremely important for economic development. A well organized and operating healthcare system constitutes an important notion for both patients and national policy. That is why the organisation of healthcare systems is the subject of reform in many countries. The aim of this study is to identify homogeneous groups of countries from the OECD in terms of the level of delivery of medical services. Countries considered in the study will be analysed through the prism of selected characteristics. The results of the study will form the basis for international comparisons and application of solutions used by countries with better healthcare systems. The study will be backed up by a chosen multivariate statistical analysis - cluster analysis.
Keywords: I10; I11; C38; 330; health sector; healthcare system; cluster analysis